MODEL PERMINTAAN UANG DI INDONESIA DENGAN PENDEKATAN VECTOR ERROR CORRECTION MODEL - Imam Mukhlis; Salman Farizi; Sariyani Sariyani; Syamsul Bachri (Quantitative Economics Journal, 2016)
This research aims to estimate the demand for money model in Indonesia for 2005.22015.12.The variables used in this research are demand for money, interest rate, inflation,and exchange rate (IDR/US$). The stationary test with ADF used to test unit root in thedata. Cointegration test applied to estimate the long run relationship between variables.This research employed the Vector Error Correction Model (VECM) to estimate the moneydemand model in Indonesia. The results showed that all the data was stationer at thedifference level (1%). There were long run relationship between interest rate, inflation andexchange rate to demand for money in Indonesia. The VECM model could not explaininteraction between explanatory variables to independent variables. In the short run, therewere not relationship between interest rate, inflation and exchange rate to demand formoney in Indonesia for 2005.2-2015.12.